2021
DOI: 10.3389/fonc.2021.691380
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Sequential Therapy of CisGem, Tislelizumab, and Lenvatinib for Advanced Intrahepatic Cholangiocarcinoma Conversion Therapy

Abstract: Intrahepatic cholangiocarcinoma (CCA), always diagnosed at an advanced stage in recent years, is of high aggression and poor prognosis. There is no standard treatment beyond first-line chemotherapy and no molecular-targeted agents or immune checkpoint inhibitors approved for advanced intrahepatic CCA. Hence, we firstly report an original therapeutic strategy for a 60-year-old patient diagnosed with intrahepatic CCA categorized as Stage IIIB (T3N1M0) by the American Joint Committee on Cancer staging system. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Lenvatinib, as a multi-kinase inhibitor of VEGF receptors 1–3, FGF receptors 1–4, platelet derived growth factor receptor α, KIT, and RET, selectively inhibits tyrosine kinase receptors involved in tumor growth and angiogenesis[ 45 ]. Tislelizumab is a PD-1 monoclonal IgG4 antibody of high affinity that is mainly used in hematological malignancies and advanced solid cancers, which was conditionally approved in China[ 45 ].…”
Section: Targeted Therapy As a Treatment Option In Cholangiocarcinoma...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lenvatinib, as a multi-kinase inhibitor of VEGF receptors 1–3, FGF receptors 1–4, platelet derived growth factor receptor α, KIT, and RET, selectively inhibits tyrosine kinase receptors involved in tumor growth and angiogenesis[ 45 ]. Tislelizumab is a PD-1 monoclonal IgG4 antibody of high affinity that is mainly used in hematological malignancies and advanced solid cancers, which was conditionally approved in China[ 45 ].…”
Section: Targeted Therapy As a Treatment Option In Cholangiocarcinoma...mentioning
confidence: 99%
“…Lenvatinib, as a multi-kinase inhibitor of VEGF receptors 1–3, FGF receptors 1–4, platelet derived growth factor receptor α, KIT, and RET, selectively inhibits tyrosine kinase receptors involved in tumor growth and angiogenesis[ 45 ]. Tislelizumab is a PD-1 monoclonal IgG4 antibody of high affinity that is mainly used in hematological malignancies and advanced solid cancers, which was conditionally approved in China[ 45 ]. Ding et al [ 45 ] reported successful neoadjuvant therapy with gemcitabine/cisplatin/lenvatinib/tislelizumab in patients with advanced intraheptic CCA followed by surgical resection with no recurrence at the 10-month follow-up[ 45 ].…”
Section: Targeted Therapy As a Treatment Option In Cholangiocarcinoma...mentioning
confidence: 99%
“…Another multicenter phase II clinical trial (NCT05620498) is currently in progress assessing the efficacy of combining Tislelizumab, Lenvatinib, and the GEMOX scheme in potentially resectable advanced BTC conversion therapy. In a recently published case report, sequential perioperative therapy of four cycles of GemCis on days 1 and 8; lenvatinib from day 1 to day 21; and tislelizumab on day 15 was found to be effective and well-tolerated [ 75 ]. The LEAP-005 (NCT03797326) ongoing study is evaluating the efficacy and safety of Lenvatinib plus Pembrolizumab in patients with previously treated advanced solid tumors.…”
Section: Clinical Studies Targeting Both Angiogenesis and Immune Chec...mentioning
confidence: 99%
“…Two case reports, with treatments including lenvatinib plus sintilimab dual therapy and systemic sequential therapy comprising GemCis, tislelizumab, and lenvatinib, had promising results in patients with advanced intrahepatic CCA. 86,87 These pieces of evidence highlight the need for more trials involving ICIs and targeted therapies to improve patient prognosis.…”
Section: Immunotherapy Plus Targeted Therapymentioning
confidence: 99%